MENYOAL ALAM, MENJELMA PEREMPUAN: KARNAVAL KULTURAL CERITA RAKYAT MORONENE - La Ode Gusman Nasiru (TELAGA BAHASA, 2020)
This research focuses on the characters in the three stories of the Moronene people, entitled: Tina Lungo (TIL); Unsono Nee Taubonto (UNT); and Duu-dunno Rema Yi Kotu'a (DRK). Using the theory of ecofeminism, this research examines the position of men and women in the Moronene ethnic communal and the extent to which the Moronene community applies their appreciation of nature. The work concept uses a qualitative descriptive analysis method. The analysis was carried out after describing the data that had been identified through the reading process. As the result, men are deliberately described with an image that is giddy, poor, and full of anger. Unlike the case with women, who can fully appreciate their oneness with nature, they are endowed with features that nurture, care for, love. In conclusion, humans need to go hand in hand with nature to create world civilization. The three stories are worth giving to children in the concept of fairy tales and bedtime. This is important so that they have ecological and gender awareness so that one day they become human beings who carry the mission of peace for the entire universe.